Eivor Andersen Oftestad: The Lateran Church in Rome and the Ark of the Covenant: Housing the Holy Relics of Jerusalem - Borgehammar, Stephan (Collegium Medievale, 2020)
An obscure twelfth-century document claiming that the main altar of the Lateran basilica in Rome has the ancient Ark of the Covenant hidden within - does that not sound more like the plot of a Hollywood spectacular than the topic of a scholarly treatise? Yet Eivor Andersen Oftestad shows how much we can learn about the hearts and minds of twelfth-century people (especially clerics) if we enter deeply into the background and ramifications of this claim, connected as it is with Jerusalem.